Recovery Ratios and Survival Times for Corporate Bonds - Izvorski, Ivailo (IMF Working Papers; Working Paper ;, 1997)
This paper analyzes the determinants of the recovery ratios and survival times (time until default) for U. S. corporate bonds. We show that seniority, the type of industry in which the firm operates, and the type of restructuring attempted after default are the major determinants of the cross-sectional distribution of individual bond recovery ratios. On an industry level, physical asset obsolescence, industry growth, and industry concentration are the most important factors. We also analyze survival times for corporate bonds and find that initial time to maturity and the general economic conditions at maturity and default explain a large fraction of the cross-sectional variation of survival times.